Media Spatialization in Indonesia’s Digital Political Econ-omy: A Case Study of Platform X through Vincent Mosco’s Framework - Herman Novry Kristiansen Paninggiran; Udi Rusadi; Dinar Anggit Wicaksana; Wahyu Mafatikhul Aulia (Brilliant International Journal Of Management And Tourism, 2025)
This study examines the dynamics of media spatialization in Indonesia’s digital political economy by analyzing selected Twitter (now X) accounts using Vincent Mosco’s theoretical framework. It explores how symbolic and algorithmic spatialization practices are employed by various digital actors, including political propagandists (@PartaiSocmed), grassroots storytellers (@txtdrberseragam), and mainstream media outlets (@detikcom and @kompascom) to shape public discourse and assert communicative power. Through a combination of critical analysis and qualitative methods, this research identifies key factors such as emotional engagement, narrative strategies, and algorithmic amplification that reinforce belief systems within digital platforms. The findings suggest that Twitter/X operates not only as a communication tool but also as a contested arena where power is negotiated and redistributed through visibility algorithms, emotional resonance, and content commodification. This study contributes to the broader field of digital political economy by offering a hybrid analytical approach that integrates Mosco’s spatialization theory with contemporary notions of algorithmic governance. It highlights how both institutional and non-institutional actors reshape symbolic power in Indonesia's evolving digital public sphere.